The BEAT-PCD (Better Experimental Approaches to Treat Primary Ciliary Dyskinesia) Clinical Research Collaboration. Issue 2 (4th February 2021) - Goutaki, Myrofora; Crowley, Suzanne; Dehlink, Eleonora; Gaupmann, René; Horton, Katie L.; Kouis, Panayiotis; Lam, Yin Ting; Loges, Niki T.; Lucas, Jane S.; Roehmel, Jobst F.; Shoemark, Amelia
The need for collaborative research networks as an effective way forward to improve diagnosis and care of rare inherited diseases is constantly highlighted and primary ciliary dyskinesia (PCD) is no exception. PCD affects 1 in 10 000 people and is genetically and clinically heterogeneous. Dysfunction of motile cilia, caused by defects in one of more than 50 genes, leads to poor mucociliary clearance and progressive upper and lower respiratory disease. Clinical symptoms include neonatal respiratory distress, chronic lung disease with bronchiectasis, rhinosinusitis and hearing impairment, and also infertility and laterality defects. 50% of patients have situs inversus and 6–12% have other defects, such as congenital cardiac disease [1, 2] The BEAT-PCD ERS CRC is a large multidisciplinary network of researchers and healthcare professionals aiming to advance clinical and translational research in different areas of primary ciliary dyskinesia building upon previous collaborative initiatives https://bit.ly/39h3veZ